Modified composite filler, preparation method thereof and application of modified composite filler in preparation of rich mineral paper master batch
Through the preparation and application of modified composite fillers, the problems of poor printing effect and insufficient physical and mechanical properties of stone paper are solved, higher printing effect and mechanical properties are achieved, dust pollution is reduced, and the compliance rate of environmental protection is improved.
Patent Information
- Application Number
- CN202411585668.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
The printing effect of existing stone paper is poor, the physical and mechanical properties are poor, and there are dust pollution problems during the production process, making it difficult to meet environmental protection requirements.
The preparation method of modified composite filler is adopted, wollastonite and light calcium carbonate are mixed after modification treatment to form a modified composite filler, and are used in the preparation of stone paper masterbatch.
It improves the printing effect and mechanical properties of stone paper, reduces dust pollution, and improves the compliance rate of environmental protection links.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic mineral fillers, and in particular to a modified composite filler and a preparation method thereof and application thereof in the preparation of stone paper masterbatch. Background Art
[0002] Stone paper is a new type of environmentally friendly material, which is between paper and plastic, also known as composite paper. It has both the performance of paper and the characteristics of plastic packaging. It can be used in packaging, printing, lunch boxes, printing inkjet and many other fields. The production cost of stone paper is lower than that of papermaking, and the raw material source is wide. From the perspective of replacing some traditional paper, it can reduce the amount of plant fiber and save a lot of forest resources; from the perspective of replacing some traditional plastic packaging, it can save a lot of strategic resources. Therefore, the emergence of stone paper has important social significance and economic value.
[0003] At present, stone paper is mainly used in the packaging industry, especially for the packaging of fruits and vegetables. Compared with the single-color plastic baskets in the past, the appearance of stone paper packaging is more in line with the current aesthetics. In addition, in addition to serving as a packaging, stone cartons can also be printed with graphics and text to serve as a promotional function. Stone paper uses fillers and resins as the main raw materials and is made by extrusion, calendering, etc. with the assistance of other additives. From the perspective of formula ingredients, fillers account for more than 70% of the formula, mainly choosing low-priced heavy calcium carbonate, which has low production costs. However, the printing effect of stone paper is not as good as that of paper made from plant fibers, and it has limited load-bearing capacity and relatively poor physical and mechanical properties. In addition, due to the late start of stone paper, stone paper manufacturers still purchase calcium carbonate for production by purchasing powder, facing dust pollution problems during the production process, and it is difficult to meet environmental protection standards. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a modified composite filler and a preparation method thereof and an application thereof in the preparation of stone paper masterbatch.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a modified composite filler, comprising the following steps:
[0007] Mixing wollastonite and a first modifier to perform a first modification to obtain modified wollastonite;
[0008] Mixing light calcium carbonate and a second modifier, performing a second modification, and obtaining modified calcium carbonate;
[0009] The modified wollastonite, modified calcium carbonate and a third modifier are mixed and subjected to a third modification to obtain the modified composite filler.
[0010] Preferably, the particle size of the wollastonite is 600-800 meshes, the whiteness of the wollastonite is ≥91%, and the mass fraction of silicon dioxide in the wollastonite is ≥52%.
[0011] Preferably, the D97 of the light calcium carbonate is 10-13 μm, the whiteness of the light calcium carbonate is ≥96%, and the oil absorption value of the light calcium carbonate is ≥45 mL / 100 g.
[0012] Preferably, the first modifier, the second modifier, and the third modifier are independently coconut oil, fatty alcohol polyoxyethylene ether, methacrylic dimethoxysilane, or methyl methacrylate;
[0013] The temperatures of the first modification, the second modification and the third modification are independently 20 to 30° C., and the times of the first modification, the second modification and the third modification are independently 0.5 to 1.5 min.
[0014] Preferably, the mass ratio of the wollastonite to the first modifier is 100:0.4-0.6; the mass ratio of the light calcium carbonate to the second modifier is 100:0.4-0.6.
[0015] Preferably, the mass ratio of the modified wollastonite to the modified calcium carbonate is 1:3-4; the mass ratio of the total mass of the modified wollastonite and the modified calcium carbonate to the mass ratio of the third modifier is 100:0.4-0.6.
[0016] The invention also provides a modified composite filler prepared by the preparation method of the modified composite filler.
[0017] The present invention also provides the use of the modified composite filler in preparing stone paper masterbatch.
[0018] Preferably, the stone paper masterbatch comprises the following components in parts by weight:
[0019] 10-20 parts of resin, 80-90 parts of modified composite filler, 1-2 parts of stearic acid, and 1-2 parts of lubricant.
[0020] Preferably, the resin is high-density polyethylene, and the lubricant is N,N'-ethylene bisstearamide or glyceryl trihydroxystearate.
[0021] The beneficial effects of the present invention are:
[0022] The present invention provides a method for preparing a modified composite filler, comprising the following steps: mixing wollastonite and a first modifier, performing a first modification, and obtaining modified wollastonite; mixing light calcium carbonate and a second modifier, performing a second modification, and obtaining modified calcium carbonate; mixing the modified wollastonite, the modified calcium carbonate, and a third modifier, performing a third modification, and obtaining a modified composite filler. The present invention selects wollastonite and light calcium carbonate for use, which can not only improve the printing effect of stone paper, but also improve the mechanical properties of stone paper compared to adding calcium carbonate alone; in addition, the present invention mixes the modified wollastonite and the modified calcium carbonate and then performs modification again, which can improve the modification effect, improve the compatibility of subsequent fillers and resins, and further improve the mechanical properties of stone paper. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing a modified composite filler, comprising the following steps:
[0024] Mixing wollastonite and a first modifier to perform a first modification to obtain modified wollastonite;
[0025] Mixing light calcium carbonate and a second modifier, performing a second modification, and obtaining modified calcium carbonate;
[0026] The modified wollastonite, modified calcium carbonate and a third modifier are mixed and subjected to a third modification to obtain the modified composite filler.
[0027] In the present invention, the preparation method of wollastonite comprises the following steps: using a jaw crusher to coarsely crush the wollastonite ore with a needle-like structure to a diameter of ≤5 cm, and then using an airflow drying method to ultrafinely grind it to obtain wollastonite; the airflow drying method is beneficial to protecting the needle-like structure of the wollastonite, and the airflow drying method adopts a normal temperature airflow pulverization process and is completed by conventional technical means in the field.
[0028] In the present invention, the particle size of the wollastonite is preferably 600-800 mesh, more preferably 650-750 mesh, and more preferably 700 mesh; the whiteness of the wollastonite is preferably ≥91%, more preferably ≥91.5%, and more preferably ≥92%; the mass fraction of silicon dioxide in the wollastonite is preferably ≥52%, more preferably ≥52.5%, and more preferably ≥53%; the aspect ratio of the wollastonite is preferably 7-10:1, more preferably 8-9:1, and more preferably 8.5:1.
[0029] In the present invention, the light calcium carbonate is purchased, the particle morphology of the light calcium carbonate is spindle-shaped, the D97 of the light calcium carbonate is preferably 10-13 μm, more preferably 10.5-12.3 μm, more preferably 11.5 μm; the whiteness of the light calcium carbonate is preferably ≥96%, further preferably ≥97%, more preferably ≥97.5%; the oil absorption value of the light calcium carbonate is preferably ≥45 mL / 100 g, further preferably ≥47 mL / 100 g, more preferably ≥50 mL / 100 g.
[0030] In the present invention, the types of the first modifier, the second modifier and the third modifier are independently preferably coconut oil, fatty alcohol polyoxyethylene ether, methacrylic dimethoxysilane (the CAS number of methacrylic dimethoxysilane is 14513-34-9) or methyl methacrylate, and the fatty alcohol polyoxyethylene ether is preferably AEO-7.
[0031] In the present invention, the temperature of the first modification, the second modification and the third modification is independently preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; the time of the first modification, the second modification and the third modification is independently preferably 0.5-1.5min, more preferably 0.7-1.3min, and more preferably 1min.
[0032] In the present invention, the mass ratio of the wollastonite to the first modifier is preferably 100:0.4-0.6, more preferably 100:0.45-0.55, and more preferably 100:0.5; the mass ratio of the light calcium carbonate to the second modifier is preferably 100:0.4-0.6, more preferably 100:0.45-0.55, and more preferably 100:0.5.
[0033] In the present invention, the mass ratio of modified wollastonite and modified calcium carbonate is preferably 1:3-4, more preferably 1:3.2-3.8, and more preferably 1:3.5; the mass ratio of the total mass of modified wollastonite and modified calcium carbonate to the third modifier is preferably 100:0.4-0.6, more preferably 100:0.45-0.55, and more preferably 100:0.5.
[0034] In the present invention, the first modification, the second modification and the third modification are carried out in a continuous modifier, and the rotation speed of the continuous modifier for the first modification, the second modification and the third modification is independently preferably 3000-3600r / min, further preferably 3100-3500r / min, and more preferably 3200-3300r / min; the modified wollastonite obtained by the first modification is conveyed to the first silo for standby use; the modified calcium carbonate obtained by the second modification is conveyed to the second silo for standby use; then, the modified wollastonite in the first silo and the modified calcium carbonate in the second silo are mixed and conveyed to the continuous modifier for the third modification. After the third modification is completed, a modified composite filler is obtained.
[0035] The invention also provides a modified composite filler prepared by the preparation method of the modified composite filler.
[0036] The present invention also provides the use of the modified composite filler in preparing stone paper masterbatch.
[0037] In the present invention, the stone paper masterbatch comprises the following components in parts by mass:
[0038] 10-20 parts of resin, 80-90 parts of modified composite filler, 1-2 parts of stearic acid, and 1-2 parts of lubricant.
[0039] In the present invention, the mass fraction of the resin is preferably 10 to 20 parts, more preferably 12 to 18 parts, and even more preferably 15 to 16 parts.
[0040] In the present invention, the mass fraction of the modified composite filler is preferably 80 to 90 parts, more preferably 82 to 87 parts, and even more preferably 84 to 85 parts.
[0041] In the present invention, the mass fraction of stearic acid is preferably 1 to 2 parts, more preferably 1.2 to 1.8 parts, and even more preferably 1.5 to 1.6 parts.
[0042] In the present invention, the mass fraction of the lubricant is preferably 1 to 2 parts, more preferably 1.2 to 1.8 parts, and even more preferably 1.5 to 1.6 parts.
[0043] In the present invention, the resin is preferably high-density polyethylene, and the high-density polyethylene is preferably high-density polyethylene 6903B produced by Yanshan Petrochemical; the lubricant is preferably N,N'-ethylene bisstearamide or glyceryl trihydroxystearate (the CAS number of glyceryl trihydroxystearate is 1323-42-8).
[0044] In the present invention, the preparation method of stone paper masterbatch comprises the following steps: adding each component to a mixer in turn for high-speed stirring, adjusting the speed of the mixer to a low speed after the high-speed stirring is completed, and conveying the mixed material obtained by high-speed stirring to a third silo, wherein the mixed material is quantitatively put into the barrel of a twin-screw extruder by an automatic weighing and batching system, extruded by the twin-screw extruder, and then the extruded material is sheared by a high-speed rotating blade using a water ring hot cutting process, and the sheared particles are conveyed into a water ring cover for cooling, and after the cooling is completed, centrifugal dehydration and air drying are sequentially performed, and after the air drying is completed, the mixed material is conveyed to the finished product silo by a conveying pipeline for packaging to obtain a stone paper masterbatch product.
[0045] In the present invention, the speed of high-speed stirring is preferably 1000-1100 r / min, more preferably 1020-1080 r / min, and more preferably 1050 r / min; the time of high-speed stirring is preferably 3-4 min, more preferably 3.2-3.8 min, and more preferably 3.5 min; when the speed of the mixer is adjusted to a low speed, the speed is preferably 50-60 r / min, more preferably 52-58 r / min, and more preferably 55 r / min; the main engine speed of the twin-screw extruder is preferably 600-700 r / min, more preferably 620-680 r / min, and more preferably 650-660 r / min; The feeding speed of the screw extruder is preferably 45-50r / min, more preferably 46-49r / min, and more preferably 47-48r / min; the temperature of each working section of the twin-screw extruder is preferably: 175°C in zone 1, 175°C in zone 2, 175°C in zone 3, 175°C in zone 4, 175°C in zone 5, 180°C in zone 6, 180°C in zone 7, 185°C in zone 8, 180°C in zone 9, and 180°C in zone 10; the head temperature of the twin-screw extruder is preferably 180-190°C, more preferably 182-188°C, and more preferably 185°C; the length of the particles obtained by shearing is preferably 3-5mm, more preferably 3.5-4.5mm, and more preferably 4mm.
[0046] In the present invention, the preparation equipment of the modified composite filler is connected with the preparation equipment of the stone paper masterbatch to form a closed and continuous system, which reduces the dust pollution in the powder packaging and powder transportation and loading and unloading processes and saves process energy consumption.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] The needle-shaped wollastonite ore was coarsely crushed by a jaw crusher until the diameter was ≤5cm, and then ultra-finely ground by airflow drying to obtain wollastonite; the particle size of the wollastonite was 600 mesh, the whiteness of the wollastonite was 92%, the mass fraction of silicon dioxide in the wollastonite was 53%, and the aspect ratio of the wollastonite was 9:1; the wollastonite and methyl methacrylate dimethoxysilane were mixed (the mass ratio of wollastonite to methyl methacrylate dimethoxysilane was 100:0.6), and the first modification was carried out in a continuous modifier, and the modification temperature was set to 25°C, the time was 1min, and the speed of the continuous modifier was 3000r / min to obtain modified wollastonite, which was transported to the first silo for standby use; the commercially available light wollastonite with a whiteness of 97.5%, an oil absorption value of 50mL / 100g, a particle size D97 of 12.3μm, and a spindle shape was prepared. Mix light calcium carbonate and methyl methacrylate dimethoxysilane (the mass ratio of light calcium carbonate and methyl methacrylate dimethoxysilane is 100:0.6), carry out the second modification in a continuous modifier, set the modification temperature to 25°C, the time to 1 min, the speed of the continuous modifier to 3000 r / min, obtain modified calcium carbonate, and transport it to the second silo for standby use; mix modified wollastonite, modified calcium carbonate and methyl methacrylate dimethoxysilane (the mass ratio of modified wollastonite and modified calcium carbonate is 1:3, and the mass ratio of the total mass of modified wollastonite and modified calcium carbonate to methyl methacrylate dimethoxysilane is 100:0.4), transport them to a continuous modifier for the third modification, set the modification temperature to 25°C, the time to 1 min, and the speed of the continuous modifier to 3000 r / min, to obtain a modified composite filler;
[0050] 12 parts of resin (high-density polyethylene 6903B), 84 parts of modified composite filler, 2 parts of stearic acid, and 2 parts of lubricant (N,N'-ethylenebisstearamide) were added to the mixer in sequence for high-speed stirring. The speed of high-speed stirring was set to 1000r / min for 4 minutes. After the high-speed stirring was completed, the speed of the mixer was adjusted to a low speed (50r / min). The mixed material obtained by high-speed stirring was transported to the third silo. In the third silo, the mixed material was quantitatively put into the barrel of the twin-screw extruder through the automatic weighing and batching system, and extruded by the twin-screw extruder (the main engine speed of the twin-screw extruder was 700r / m in, the feeding speed is 50r / min, the head temperature is 180℃, the temperature of each working section is: zone 1 175℃, zone 2 175℃, zone 3 175℃, zone 4 175℃, zone 5 175℃, zone 6 180℃, zone 7 180℃, zone 8 185℃, zone 9 180℃, zone 10 180℃), then the extruded material is sheared by a water ring hot cutting process with a high-speed rotating blade, and the sheared particles (length 3mm) are sent to a water ring cover for cooling. After cooling, centrifugal dehydration and air drying are carried out in sequence. After air drying, they are transported to the finished product silo by a conveying pipeline for packaging to obtain stone paper masterbatch products.
[0051] Example 2
[0052] The needle-shaped wollastonite ore was coarsely crushed by a jaw crusher until the diameter was ≤5cm, and then ultra-finely ground by airflow dry grinding to obtain wollastonite; the particle size of the wollastonite was 700 mesh, the whiteness of the wollastonite was 91%, the mass fraction of silicon dioxide in the wollastonite was 52%, and the aspect ratio of the wollastonite was 8:1; the wollastonite and AEO-7 were mixed (the mass ratio of wollastonite to AEO-7 was 100:0.5), and the first modification was carried out in a continuous modifier, and the modification temperature was set to 25°C, the time was 1min, and the speed of the continuous modifier was 3200r / min to obtain modified wollastonite, which was transported to the first silo for standby use; the commercially available wollastonite with a whiteness of 97%, an oil absorption value of 45mL / 100g, a particle size D97 of 10.5μm, and a spindle The light calcium carbonate in bulk form is mixed with AEO-7 (the mass ratio of light calcium carbonate to AEO-7 is 100:0.5), and the second modification is carried out in a continuous modifier, and the modification temperature is set to 25°C, the time is 1 min, and the speed of the continuous modifier is 3000 r / min, to obtain modified calcium carbonate, which is transported to the second silo for standby use; the modified wollastonite, modified calcium carbonate and AEO-7 are mixed (the mass ratio of modified wollastonite to modified calcium carbonate is 1:4, and the mass ratio of the total mass of modified wollastonite and modified calcium carbonate to AEO-7 is 100:0.5), and transported to a continuous modifier for the third modification, and the modification temperature is set to 25°C, the time is 1 min, and the speed of the continuous modifier is 3000 r / min, to obtain a modified composite filler;
[0053] 10 parts of resin (high-density polyethylene 6903B), 84 parts of modified composite filler, 2 parts of stearic acid, and 2 parts of lubricant (glycerol trihydroxystearate) were added to the mixer in sequence for high-speed stirring. The speed of high-speed stirring was set to 1100r / min for 3 minutes. After the high-speed stirring was completed, the speed of the mixer was adjusted to a low speed (60r / min). The mixed material obtained by high-speed stirring was transported to the third silo. In the third silo, the mixed material was quantitatively put into the barrel of the twin-screw extruder through the automatic weighing and batching system, and extruded by the twin-screw extruder (the main engine speed of the twin-screw extruder was 600r / min). The feeding speed is 50r / min, the head temperature is 180℃, the temperatures of each working section are: zone 1 175℃, zone 2 175℃, zone 3 175℃, zone 4 175℃, zone 5 175℃, zone 6 180℃, zone 7 180℃, zone 8 185℃, zone 9 180℃, zone 10 180℃), then the extruded material is sheared by a water ring hot cutting process with a high-speed rotating blade, and the sheared particles (length 4mm) are sent to a water ring cover for cooling. After cooling, they are centrifuged and air-dried in sequence. After air-drying, they are transported to the finished product silo by a conveying pipeline for packaging to obtain stone paper masterbatch products.
[0054] Comparative Example 1
[0055] The needle-shaped wollastonite ore was coarsely crushed by a jaw crusher to a diameter of ≤5cm, and then ultra-finely ground by a jet mill dry method to obtain wollastonite; the particle size of the wollastonite was 700 mesh, the whiteness of the wollastonite was 91%, the mass fraction of silicon dioxide in the wollastonite was 52%, and the aspect ratio of the wollastonite was 8.5:1; the wollastonite and AEO-7 were mixed (the mass ratio of wollastonite to AEO-7 was 100:1), and the first modification was carried out in a continuous modifier, and the modification temperature was set to 25°C, the time was 1min, and the speed of the continuous modifier was 3000r / min to obtain the modified wollastonite, which was then transported to The mixture is placed in the first silo for standby use; light calcium carbonate with a commercial whiteness of 97%, an oil absorption value of 45 mL / 100 g, a particle size D97 of 10.5 μm, and a spindle shape is mixed with AEO-7 (the mass ratio of light calcium carbonate to AEO-7 is 100:1), and a second modification is performed in a continuous modifier, and the modification temperature is set to 25°C, the time is 1 min, and the speed of the continuous modifier is 3000 r / min to obtain modified calcium carbonate, which is transported to the second silo for standby use; modified wollastonite and modified calcium carbonate (the mass ratio of modified wollastonite to modified calcium carbonate is 1:3) are mixed to obtain a modified mixed powder;
[0056] 10 parts of resin (high-density polyethylene 6903B), 84 parts of modified mixed powder, 2 parts of stearic acid, and 2 parts of lubricant (glycerol trihydroxystearate) were added to the mixer in sequence for high-speed stirring. The speed of high-speed stirring was set to 1100r / min for 3 minutes. After the high-speed stirring was completed, the speed of the mixer was adjusted to a low speed (60r / min). The mixed material obtained by high-speed stirring was transported to the third silo. In the third silo, the mixed material was quantitatively put into the barrel of the twin-screw extruder through the automatic weighing and batching system, and extruded by the twin-screw extruder (the main engine speed of the twin-screw extruder was 600r / min). The feeding speed is 50r / min, the head temperature is 180℃, the temperature of each working section is: zone 1 175℃, zone 2 175℃, zone 3 175℃, zone 4 175℃, zone 5 175℃, zone 6 180℃, zone 7 180℃, zone 8 185℃, zone 9 180℃, zone 10 180℃), then the extruded material is sheared by a water ring hot cutting process with a high-speed rotating blade, and the sheared particles (3mm in length) are sent to a water ring cover for cooling. After cooling, centrifugal dehydration and air drying are carried out in sequence. After air drying, they are transported to the finished product silo by a conveying pipeline for packaging to obtain stone paper masterbatch products.
[0057] Comparative Example 2
[0058] The commercially available light calcium carbonate with a whiteness of 97%, an oil absorption value of 45 mL / 100 g, a particle size D97 of 10.5 μm, and a spindle shape was mixed with AEO-7 (the mass ratio of light calcium carbonate to AEO-7 was 100:1), and modified in a continuous modifier, the modification temperature was set to 25° C., the time was set to 1 min, and the speed of the continuous modifier was set to 3000 r / min to obtain modified calcium carbonate;
[0059] 12 parts of resin (high-density polyethylene 6903B), 86 parts of modified calcium carbonate, 2 parts of stearic acid, and 2 parts of lubricant (glycerol trihydroxystearate) were added into a mixer in sequence for high-speed stirring. The speed of high-speed stirring was set to 1000 r / min for 4 minutes. After the high-speed stirring was completed, the speed of the mixer was adjusted to a low speed (50 r / min). The mixture obtained by high-speed stirring was transported to the third silo. In the third silo, the mixture was quantitatively put into the barrel of the twin-screw extruder by an automatic weighing and batching system, and extruded by the twin-screw extruder (the main engine speed of the twin-screw extruder was 600 r / min, The feeding speed is 50r / min, the head temperature is 180℃, and the temperatures of each working section are: zone 1 175℃, zone 2 175℃, zone 3 175℃, zone 4 175℃, zone 5 175℃, zone 6 180℃, zone 7 180℃, zone 8 185℃, zone 9 180℃, zone 10 180℃). Then the extruded material is sheared by a high-speed rotating blade using a water ring hot cutting process, and the sheared particles (with a length of 4mm) are sent to a water ring cover for cooling. After cooling, centrifugal dehydration and air drying are carried out in sequence. After air drying, they are transported to the finished product silo by a conveying pipeline for packaging to obtain stone paper masterbatch products.
[0060] Comparative Example 3
[0061] Commercially available heavy calcium carbonate with a whiteness of 93% and a particle size D97 of 10.5 μm was mixed with AEO-7 (the mass ratio of heavy calcium carbonate to AEO-7 was 100:1), and modified in a continuous modifier. The modification temperature was set to 25° C., the time was set to 1 min, and the speed of the continuous modifier was set to 3600 r / min to obtain modified heavy calcium carbonate;
[0062] 12 parts of resin (high-density polyethylene 6903B), 86 parts of modified heavy calcium carbonate, 2 parts of stearic acid, and 2 parts of lubricant (N,N'-ethylenebisstearamide) were added to the mixer in sequence for high-speed stirring. The high-speed stirring speed was set to 1000r / min for 4 minutes. After the high-speed stirring was completed, the speed of the mixer was adjusted to a low speed (50r / min). The mixed material obtained by high-speed stirring was transported to the third silo. In the third silo, the mixed material was quantitatively put into the barrel of the twin-screw extruder through the automatic weighing and batching system, and extruded by the twin-screw extruder (the main engine speed of the twin-screw extruder was 700r / m in, the feeding speed is 50r / min, the head temperature is 180℃, the temperature of each working section is: zone 1 175℃, zone 2 175℃, zone 3 175℃, zone 4 175℃, zone 5 175℃, zone 6 180℃, zone 7 180℃, zone 8 185℃, zone 9 180℃, zone 10 180℃), then the extruded material is sheared by a water ring hot cutting process with a high-speed rotating blade, and the sheared particles (length 3mm) are sent to a water ring cover for cooling. After cooling, centrifugal dehydration and air drying are carried out in sequence. After air drying, they are transported to the finished product silo by a conveying pipeline for packaging to obtain stone paper masterbatch products.
[0063] The stone paper masterbatch products prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were used in the production of stone paper according to the following formula: 83 parts of stone paper masterbatch products, 15 parts of high-density polyethylene 6903B, and 2 parts of additives (the additives include 1 part of plasticizer and 1 part of stabilizer, the plasticizer is paraffin, and the stabilizer is calcium zinc stabilizer). Sheet samples of the same thickness were prepared by calendering process. The tensile strength, tear strength and folding endurance were tested according to the national standards GB / T453-2002, GB / T455-2002, and GB / T457-2008. The ink absorption was reflected by the ink transfer rate. The test conditions of the ink transfer rate were as follows: Epson R230 was used as the printing output device, and the GATF standard scale was printed on the selected paper sample. Then, the printed pattern of each sample was transferred to a white polyester T-shirt using a magnetic heat transfer machine. After the transfer ink was dried, the quality change of the paper sample before and after the transfer was tested. f represents the ink transfer rate, m0 represents the sample quality before inkjet printing, m1 represents the sample quality after inkjet printing, m2 represents the quality of the sample after transfer, and the ink transfer rate f = (m1-m2) / (m1-m0)×100%. Finally, the performance test results of different samples are obtained, as shown in Table 1.
[0064] Table 1 Performance test results of different samples
[0065] Performance Indicators Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength N / mm 12.3 12.1 11.5 9.5 9.8 Tear strength / mN 253 251 235 189 193 Folding endurance / times 244 237 226 186 192 Ink transfer rate / % 51.2 52.3 50.6 47.6 43.7
[0066] As shown in Table 1, the tensile strength, tear strength, folding endurance and ink transfer rate of the samples obtained in Examples 1 to 2 are better than those in Comparative Examples 1 to 3, indicating that the combination of wollastonite and light calcium carbonate can not only improve the printing effect of stone paper, but also improve the mechanical properties of stone paper compared with the addition of single calcium carbonate. In addition, mixing the modified wollastonite with the modified calcium carbonate and modifying it again (Examples 1 and 2) is more conducive to improving the compatibility of the powder and the resin than directly mixing the modified wollastonite with the modified calcium carbonate without modification (Comparative Example 1). Moreover, from the perspective of ink transfer rate, the printing effects are in the order of wollastonite + light calcium carbonate > light calcium carbonate > heavy calcium carbonate.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified composite filler, characterized in that: It includes the following steps: Mixing wollastonite and a first modifier to perform a first modification to obtain modified wollastonite; Mixing light calcium carbonate and a second modifier, performing a second modification, and obtaining modified calcium carbonate; The modified wollastonite, modified calcium carbonate and a third modifier are mixed and subjected to a third modification to obtain the modified composite filler.
2. The method for preparing the modified composite filler according to claim 1, characterized in that: The particle size of the wollastonite is 600-800 meshes, the whiteness of the wollastonite is ≥91%, and the mass fraction of silicon dioxide in the wollastonite is ≥52%.
3. The method for preparing the modified composite filler according to claim 1 or 2, characterized in that: The D97 of the light calcium carbonate is 10-13 μm, the whiteness of the light calcium carbonate is ≥96%, and the oil absorption value of the light calcium carbonate is ≥45 mL / 100 g.
4. The method for preparing the modified composite filler according to claim 3, characterized in that: The types of the first modifier, the second modifier and the third modifier are independently coconut oil, fatty alcohol polyoxyethylene ether, methacrylic dimethoxysilane or methyl methacrylate; The temperatures of the first modification, the second modification and the third modification are independently 20 to 30° C., and the times of the first modification, the second modification and the third modification are independently 0.5 to 1.5 min.
5. The method for preparing the modified composite filler according to claim 4, characterized in that: The mass ratio of the wollastonite to the first modifier is 100:0.4-0.6; the mass ratio of the light calcium carbonate to the second modifier is 100:0.4-0.
6.
6. The method for preparing the modified composite filler according to claim 5, characterized in that: The mass ratio of the modified wollastonite to the modified calcium carbonate is 1:3-4; the mass ratio of the total mass of the modified wollastonite and the modified calcium carbonate to the mass ratio of the third modifier is 100:0.4-0.
6.
7. A modified composite filler prepared by the method for preparing a modified composite filler according to any one of claims 1 to 6.
8. Use of the modified composite filler according to claim 7 in the preparation of stone paper masterbatch.
9. The use according to claim 8, characterized in that The stone paper masterbatch comprises the following components in parts by weight: 10-20 parts of resin, 80-90 parts of modified composite filler, 1-2 parts of stearic acid, and 1-2 parts of lubricant.
10. The use according to claim 9, characterized in that The resin is high-density polyethylene, and the lubricant is N,N'-ethylenebisstearamide or glyceryl trihydroxystearate.